ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT. SINAR GALESONG MANDIRI - Sitti Zulaeha; Ayu Puspita Sari (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
Analysis of Factors Affecting Accounting Information System Performance at PT. Sinar Galesong Mandiri, Thesis Accounting Study Program Faculty of Economics and Business Muhammadiyah University Makassar. Supervised by Supervisor I Ansyarif Khalid and Supervisor II Sitti Zulaeha. This study aims to obtain empirical evidence using primary data regarding Factors Affecting Accounting Information System Performance at PT. Sinar Galesong Mandiri. This type of research used in research is correlational with a quantitative approach. The population and sample in this study are based on certain criteria or puposive sampling techniques of 43 respondents. The results showed that the user involvement variable had no significant effect on the performance of accounting information systems. While a variety of training and education program variables, personal technical abilities, facilities and top management support significantly influence the performance of accounting information systems.